FcγRIIB signals inhibit BLyS signaling and BCR-mediated BLyS receptor up-regulation - Crowley, Jenni E. (American Society of Hematology, 2009)
These studies investigate how interactions between the BCR and FcγRIIB affect B lymphocyte stimulator (BLyS) recep-tor expression and signaling. Previous studies showed that BCR ligation up-regulates BLyS binding capacity in mature B cells, reflecting increased BLyS receptor levels. Here we show that FcγRIIB coaggregation dampens BCR-induced BLyS receptor up-regulation. This cross-regulation requires BCR and FcγRIIB coligation, and optimal action relies on the Src-homology-2 (SH2)–containing inositol 5 phosphase-1 (SHIP1). Subsequent to FcγRIIB/BCR coaggregation, the survival promoting actions of BLyS are attenuated, reflecting reduced BLyS receptor signaling capacity in terms of Pim 2 maintenance, noncanonical NF-κB activation, and Bcl-xL levels. These findings link the negative regulatory functions of FcγRIIB with BLyS-mediated B-cell survival.